Respuesta :

umyaa

Answer:

−3y2−8y−12

Step-by-step explanation:

Let's simplify step-by-step.

−5y2−9y−4−(−2y2−y+8)

Distribute the Negative Sign:

=−5y2−9y−4+−1(−2y2−y+8)

=−5y2+−9y+−4+−1(−2y2)+−1(−y)+(−1)(8)

=−5y2+−9y+−4+2y2+y+−8

Combine Like Terms:

=−5y2+−9y+−4+2y2+y+−8

=(−5y2+2y2)+(−9y+y)+(−4+−8)

=−3y2+−8y+−12

Answer:

[tex]-3y^2-8y-12[/tex]

Step-by-step explanation:

Simplify each term.

[tex]-5y^2-9y-4+2y^2+y-8[/tex]

Simplify by adding terms.

[tex]-3y^2-8y-12[/tex]

hope this helps :)